The Effect of Discipline and Work Environment on Teacher Performance at SMK Sasmita Jaya I In Pamulang - Muhammad Ramdhan (Universitas Negeri Makassar, 2019)
This study aims to determine the effect of discipline and work environment on teacher performance at SMK Sasmita Jaya I in Pamulang. The method used is explanatory research with analytical techniques using statistical analysis with regression, correlation, determination, and hypothesis testing. The results of this study that discipline has a significant effect on teacher performance by 45.4%, hypothesis testing is obtained t count > t table or (7.631 > 1.989). The work environment significantly affects teacher performance by 44.9%; hypothesis testing is obtained t count > t table or (7,560 > 1,989). Discipline and work environment simultaneously significantly affect teacher performance with the regression equation Y = 9.081 + 0.393X1 + 0.444X2. The influence contribution is 61.1%, hypothesis testing is obtained by F arithmetic > F table or (54.243 > 2.710).